INFORMAL COMPONENT IN THE EDUCATIONAL WORK WITH GIFTED CHILDREN IN CHINA - Kalashnyk, Lyubov; Burtseva, Yulia; Naumenko, Stanislav; Wu, Yanlin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Informal Education is a general term for education that can occur outside of a structured curriculum. Nowadays it is mainly used to provide people of different ages and social categories with additional knowledge and skills needed for their professional activity or fulfilling interest. China today also uses such kind of providing educational services mainly for children and youths. These activities are seen by the state educational system as the basic level of gifted children`s detection and separating them from the other ones. Modern Chinese educational theory has its own ideas as to the problem of gifted children starting from the definition of giftedness and up to the place of such children in the society including the welfare and legal issues. Seeing giftedness as “ability to work and methodical training” the Chinese educational and welfare system is totally built up by this conception. The article using various research methods (such as theoretical literature and current Chinese legislation`s analysis, comparative methods, method of personal experience etc.) represents the Chinese experience as to educational work with gifted children especially in the field of informal education as well as general ideas of the Giftedness theory in the Chinese educational practice.